Results of a Conservative Management of Minimally Displaced Lateral Condyle of Humerus Fracture in Children - Shrestha, DK; Bastola, P; Dhungel, B; Lakhanpal, VP (Journal of Nepalgunj Medical College, 2015)
Background: Fracture of lateral condyle humerus in pediatric population is second most common elbow injury. There is controversy regarding treatment of minimally displaced (less than 2mm) fracture. If this group can be taken care with non operative treatment it will be an easier and lot cheaper option especially for rural parts of west Nepal. Aim: To see the viability of treatment of minimally displaced lateral condyle humerus fracture with non operative treatment and look for short and immediate results. Methodology: This was a prospective observational, hospital based study carried out in Nepalgunj Medical College teaching Hospital from Jan. 2013 - Jan. 2014. In children between 2.5 - 13 years, with minimally displaced fracture of lateral condyle humerus were radiologically followed up for 12 weeks. All patients underwent long arm cast and serial radiographs in follow ups. At 12 weeks; range of motion, tenderness and carrying angle were looked for. Results: There were 12 patients in the study with average age of 6.95 years, range (SD 2.92). There were no displacements in follow ups. At 6 weeks all had full range of motion and at 12 weeks all had full range of motion without tenderness. Three kids had approximately 5 degrees of carrying angle change on other side to varus. Conclusion: Non operative treatment with 4 weeks of long arm cast in supination is a good alternative option for minimally displaced lateral condyle fracture humerus. A good follow up of the treated patients is an integral part of management along with radiological evidence. Parents need to be warned about bump in the lateral side during healing. Journal of Nepalgunj Medical College Vol.12(1) 2014: 10-13